Service Level Agreements Compliance in 5G Network Slicing: An Analysis of Resource Allocation Strategies - Costa, Wanderson L.; Gomes, Rafael L. (Anais do Latin-American Symposium on Dependable Computing (LADC); 2025: Anais do XIV Latin-American Symposium on Dependable Computing, 2025)
5G networks are designed to support a wide range of applications and services with heterogeneous performance requirements, where Network Slicing enables the creation of logically isolated slices to meet specific Service Level Agreements (SLAs). Resource allocation strategies ensure that the network dynamically and intelligently provisions bandwidth, computing, and storage resources to each slice based on its SLA constraints. However, there is an existing gap in the literature regarding the systematic and comparative evaluation of the performance implications of resource allocation strategies. Within this context, this paper presents a comprehensive and comparative evaluation of SLA compliance for service delivery slices in 5G networks, from the perspective of resource allocation strategies. Results of the experiments performed, using TCP and UDP traffic and KPI collection, show how different policies affect SLA compliance in terms of throughput, delay, and jitter, highlighting the trade-offs between priority, fairness, and spectral efficiency.